Wound healing in glaucoma surgery. Part 1. Wound healing morphology - N. S. Izmailova; S. Yu. Petrov; A. D. Dzebisova (Российский офтальмологический журнал)
Glaucoma is a leading cause of blindness in the world. A proven condition for preventing the progression of glaucomatous optic neuropathy is to reduce intraocular pressure. Therapy begins with local hypotensive drugs; if they are ineffective, laser treatment or surgery is used. However, hypotensive intervention does not guarantee a stable hypotensive effect. Wound healing is a complex physiological dynamic process that is necessary to maintain homeostasis in the body. This process includes three interrelated phases: inflammation, fibroplasia, and remodulation (maturation) of the scar. Thе review presents various cellular mechanisms involved in the regulation of these processes and factors that contribute to excessive scarring. The review presents various cellular mechanisms involved in the regulation of these processes and contributing to excessive scarring. Current knowledge about the key factors of pathomorphological processes occurring in the filtration zone is intended to stimulate the development of new methods for prolonging the effect of filtering surgery.